Implikasi Pola Koalisi Partai Politik terhadap Dinamika Penyelenggaraan Pemilihan Presiden Indonesia - Ahmad Siboy (Faculty of Law Hang Tuah University, 2021)
The coalition of political parties in nominating the presidential and vice-presidential candidate pair is a necessity. This is because none of the political parties received a majority vote, making them need support from other parties to meet the presidential threshold requirement. However, the established coalition mostly is not based on the same vision, mission, and ideology. The coalition is based on the developed political situations and conditions or for power-sharing such as sharing ministerial seats. As a result, the composition of the coalition in each presidential election always changes. This is obviously a coalition pattern that is oriented only to pragmatism. The research problems in this study were as follows. (1) What is the basis of the coalition of political parties in Indonesia? (2) What is the pattern of political party coalitions in Indonesia? (3) Why does a permanent coalition pattern between political parties need to occur? This study analyzed the coalition pattern of political parties and its implications for the implementation of the presidential election in Indonesia. The results showed that the coalition pattern of political parties in Indonesia occurred because most of the political parties do not make their vision, mission, and ideology become the basis for determining the direction of the coalition. Political parties build coalitions based on the agreement for a certain number of ministerial seats promised by the presidential and vice-presidential candidate pairs that they nominate. Political parties that were previously rivals (from the winning presidential and vice-presidential candidate pairs) can transfer their supporting positions to the elected presidential and vice-presidential candidate pairs. In fact, a permanent coalition is highly needed to ensure a check and balance of the winner of the general election. This means that the composition of political parties supporting the losing presidential and vice-presidential candidate pairs must be ready to become parties in the opposition ranks, not to become government coalition parties.